Animais aquáticos de importância médica no Brasil - Haddad Júnior, Vidal [UNESP] (FapUNIFESP (SciELO), 2003)
The injuries caused by venomous and poisonous aquatic animals may provoke important morbidity in the victim. The cnidarians (jellyfishes, especially cubomedusas and Portuguese-Man-of-War) caused nearly 25% of 236 accidents by marine animals, while sea urchins were responsible for about 50% and catfish, stingrays and scorpionfish nearly 25%). In freshwater, stingrays and catfish cause injuries with a very similar mechanism to the poisoning and the effects of the toxins of marine species. In a series of about 200 injuries observed among freshwater fishermen, nearly 40% were caused by freshwater catfish, 5% freshwater stingrays and 55% by traumatogenic fish, such as piranhas and trairas. The author presents the aquatic animals that cause injuries to humans in Brazil, the clinical aspects of the envenoming and the first measures for the control of the severe pain observed mainly in the accidents caused by cnidarians and venomous fishes.
Aquatic animals of medical importance in Brazil
Keywords: Brazil; Cnidarians; Sea urchins; Traumatogenic aquatic animals; Venomous aquatic animals; Venomous fishes; toxin; catfish; human; injury; intoxication; jellyfish; mollusc; morbidity; sea urchin; sponge (Porifera); Accidents; Animals; Bites and Stings; Cnidaria; Cnidarian Venoms; Fish Venoms; Fishes, Poisonous; Humans; Animalia; Characiformes; Dasyatidae; Echinoidea; Mollusca; Physalia physalia; Pisces; Porifera; Potamotrygon motoro; Scyphozoa; Siluridae